Patents as Early Indicators of Technology and Investment Trends: Analyzing the Microbiome Space as a Case Study - Fankhauser, Manuel; Moser, Christian; Nyfeler, Theodor (Frontiers in Bioengineering and Biotechnology, 2018)
The human microbiome is the collective of microbes living in symbiosis on and within humans. Modulating its composition and function has become an attractive means for the prevention and treatment of a variety of diseases including cancer. Since the initiation of the human microbiome project in 2007, the number of academic publications and active patent families around the microbiome has grown exponentially. Screening patent databases can be useful for the early detection and the tracking of new technology trends. However, it is not sufficient to assess portfolio sizes because emerging players with small but high-quality patent portfolios will be missed within the noise of large but low-quality portfolio owners. Here we used the consolidated database and software tool PatentSight to benchmark patent portfolios, and to analyze key patent owners and innovators of the microbiome space. Our study shows how in-depth patent analyses combining qualitative and quantitative parameters can identify actionable early indicators of technology and investment trends from large patent datasets. The resulting insights are suitable for further evaluations by more targeted approaches applied in classical due diligence processes.